The UNESCO WINISIS software analysis of usage in the Philippines (1999-2005) - Ramos, Alana G. (2006)
UNESCO developed the Computerized Documentation System/Integrated Set of Information Systems, or CDS/ISIS, which was launched and distributed for free to libraries and information centers in member countries in 1985. All in all, worldwide users could total more than 20,000. They are located mostly in the Asia-Pacific region, Africa, Latin America and the Caribbean.